AB0142 Mycophenolate mofetil and sirolimus inhibit proliferation of primary human osteoblasts in vitro. (23rd January 2014) - Stracke, S.; Ramudo, L.; Aymanns, C.; Ernst, F.; Fiene, B.; Fiene, M.
Abstract : Background: Maintenance of bone homeostasis depends on the coupling between the activity of osteoblasts and osteoclasts that is locally regulated by B cells and T cells. Thus, both autoimmune diseases and immunosuppressive therapy can influence bone metabolism and bone turnover. Calcineurin inhibitors can induce high turnover osteopathy, with and without bone loss. There are only limited data on the influence of other immunosuppressants such as mycophenolate mofetil (MMF) and mTOR inhibitors (sirolimus) on bone turnover and osteoblast proliferation. Objectives: We analyzed the antiproliferative capacity of cyclosporine (CsA), MMF and sirolimus (sir) on primary human osteoblasts (hOB) and human osteosarcoma cells (TE85 cell line) in vitro . Methods: hOB ad TE8-cells were cultured under standardized conditions with serum stimulation. Sirolimus and MMF were added in ascending concentrations of 1 – 100 μg/L and cyclosporine was given at 100 – 1000 μg/L for 24 hours. The antiproliferative capacity was measured by MTT-assay and compared to serum-stimulated controls. Results: MMF dose-dependently inhibited the proliferation of primary hOB. We saw a growth inhibition to 92% [at 1 μg/L MMF], 84% [at 10 μg/L MMF] and 69% respectively [at 100 μg/L MMF]. Sirolimus already inhibited hOB growth at the lowest concentration used. Cell growth was reduced to 69% compared to control cells [at 1 μg/L sir], 74% [at 10 μg/L sir] and 70% respectively [at 100 μg/L sir]. Also cyclosporine showed an inhibitory effect on hOB proliferation, however, only at higher doses: 93% [at 100 μg/L CsA], 84% [at 500 μg/L CsA], 77% [at 1000 μg/L CsA]. In the osteosarcoma cell line TE85, cyclosporine and sirolimus were without effect while MMF showed an inhibition of proliferation at the highest dose used: reduction to 83% cell growth [at 100 μg/L MMF]. Conclusions: At doses used in clinical routine, sirolimus [1 μg/L] and MMF [10 μg/L] inhibited the proliferative capacity of primary human osteoblasts in vitro . Sirolimus and MMF may contribute to bone loss in autoimmune diseases via inhibition of osteoblast growth. Disclosure of Interest: None Declared